2000
DOI: 10.1088/0953-4075/33/5/303
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic study of the electronic structure and 5d orbital of La confined inside a C60fullerene cage

Abstract: We determine the electronic structure of the metallofullerene La@C 60 for different configurations of La, namely 5d6s 2 , 5d 2 6s and 4f5d6s. The fullerene environment is modelled by a confining potential V c (r), equivalent to an attractive spherical square well of depth −8.22 eV and width 1.89 au. The atomic orbitals of La are obtained by solving numerically the Dirac-Fock equations including V c (r). For both configurations 5d6s 2 and 4f5d6s, La donates two electrons to the fullerene molecule, while in 5d 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…The observed phenomenon was named (Connerade et al, 1999b) ''selective orbital compression'' (SOC). Note, SOC was also witnessed (Connerade and Semauone, 2000b) for the 5d orbital in the 5d6s 2 ; 2 D 3=2;5=2 ground-state of @La from La@C 60 :…”
Section: Selective Orbital Compressionmentioning
confidence: 95%
See 1 more Smart Citation
“…The observed phenomenon was named (Connerade et al, 1999b) ''selective orbital compression'' (SOC). Note, SOC was also witnessed (Connerade and Semauone, 2000b) for the 5d orbital in the 5d6s 2 ; 2 D 3=2;5=2 ground-state of @La from La@C 60 :…”
Section: Selective Orbital Compressionmentioning
confidence: 95%
“…The potential (5) was later on employed by Xu et al (1996) to interpret physics hidden behind observed oscillations in the photoionization cross section of the C 60 cage itself. To date, the model potential (5) has found useful applications in a number of investigations of structure and photoionization of thus simulated endohedral atoms A@C 60 (Connerade et al, 1999a(Connerade et al, , b, 2000b(Connerade et al, , c, 2001Connerade and Semauone, 2000b;Dolmatov et al, 2002) where a number of important findings were revealed. To list a few of them, the prediction of unusual level crossings and degeneracies resulting in avoided energy level crossings, exemplified by the H@C 60 formation (Connerade et al, 1999a), the appearance of confinement resonances in photoionization cross sections of A@C 60 atoms (Connerade et al, 1999b, effects of selective compression of the atomic orbital by an attractive shell (Connerade et al, 1999b;Connerade and Semauone, 2000b), the significant redistribution of oscillation strengths and ''reversed'' action of electron correlation in @A atoms compared to free atoms (Connerade et al, 1999b), etc.…”
Section: Preliminariesmentioning
confidence: 99%
“…The encapsulating ("confining") cage is approximated as a spherical square well [8][9][10][11]16] and has the functional form…”
Section: On-center Calculationsmentioning
confidence: 99%
“…The well depth is adjusted so that the model reproduces the electronic behavior of a single electron in the jellium shell as calculated from first principles [8] or the photoionization behavior of other caged species. [9][10][11]16] We chose the latter parameters due to the similarity of the models involved. Now Equation (3) must be discretized in order to pursue a numerical solution.…”
Section: On-center Calculationsmentioning
confidence: 99%
See 1 more Smart Citation